Utility of D-dimer and other biomarkers in COVID-19 patients - A prospective study in a tertiary care center - A, Indira Priyadarshini; K, Jayalaxmi Yadav; SH, Shridevi; C, Bharat (Journal of Pathology of Nepal, 2022)
Background: Clinical status and concurrent comorbidities of COVID-19 patients largely determine the need for their admittance to ICUs, similarly, several laboratory parameters like D-dimer, LDH, serum ferritin, CRP, and IL-6 may facilitate the assessment of disease severity and rational triaging. Therefore, their role in the management of COVID-19 patients has to be assessed. Materials and methods: Prospective study was done on patients who were tested positive for COVID-19 infection and admitted to various centers under the Vijayanagara Institute of Medical Sciences, India. Patients were divided into mild, moderate, and severe cases. Demographic data and serum levels of biomarkers like D-dimer, LDH, ferritin, CRP, and IL-6 were collected in these patients, and data were statistically analyzed. Results: A total of 164 cases were included in this study, of which, 62 were mild, 47 moderate, and 55 were severely infected COVID-19 patients. There was male predominance in patients infected with COVID-19. The median age of presentation was 53, 60, and 57 years in mild, moderate, and severe cases respectively. Median was also derived for D-dimer, LDH, serum ferritin, CRP, and IL-6 in mild, moderate, and severe cases. Changes in D-dimer, LDH, and serum ferritin levels in mild, moderate, and severe cases showed statistical significance(p<0.05). Conclusions: D-dimer helps in the early identification of mild, moderate, and severe cases and can be used for the vigilant monitoring of patients. LDH and serum ferritin helps in the identification of oxygen-dependent and oxygen-independent patients. The role of CRP and IL-6 in the management of COVID-19 patients has to be further investigated.